Psychoanalysis, International Relations, and Diplomacy : a Sourcebook on Large-Group Psychology. - Volkan, Vamik D. (Karnac Books, 2014)
The author has three goals in writing this book. The first is to explore large-group identity such as ethnic identity, diplomacy, political propaganda, terrorism and the role of leaders in international affairs. The second goal is to describe societal and political responses to trauma at the hands of the Other, large-group mourning, and the appearance of the history of ancestors and its consequences. The third goal is to expand theories of large-group psychology in its own right and define concepts illustrating what happens when tens of thousands or millions of people share similar psychologica.